2018
DOI: 10.3390/aerospace5040118
|View full text |Cite
|
Sign up to set email alerts
|

Crack Growth in a Range of Additively Manufactured Aerospace Structural Materials

Abstract: The aerospace industry is now beginning to adopt Additive Manufacturing (AM), both for new aircraft design and to help improve aircraft availability (aircraft sustainment). However, MIL-STD 1530 highlights that to certify airworthiness, the operational life of the airframe must be determined by a damage tolerance analysis. MIL-STD 1530 also states that in this process, the role of testing is merely to validate or correct the analysis. Consequently, if AM-produced parts are to be used as load-carrying members, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 41 publications
(123 reference statements)
2
51
0
Order By: Relevance
“…The main analyses methods used in the present paper are described in detail [17], and also in the subsequent sections.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The main analyses methods used in the present paper are described in detail [17], and also in the subsequent sections.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, Cao, Zhang, Ryde, and Lados [24] presented an early review of cracking in AM Ti-6Al-4V, where fatigue thresholds associated with the different AM processes were carefully assessed. References [3,16,17,21] subsequently revealed that crack growth in a range of AM materials could be represented by the Hartman-Schijve (HS) variant of the NASGRO crack growth equation, viz:…”
Section: Crack Growth In Am Ti-6al-4vmentioning
confidence: 99%
See 2 more Smart Citations
“…Applications to bridge and rail steels are given in [50][51][52], to polymers in [53] and to bonded wooden joints in [54]. Equation (1) has also been shown to be able to represent the growth of both long and small cracks in additively-manufactured materials [55][56][57], to laser additive deposition (LAD) and cold spray repairs to metallic structures [58,59]. A feature of this formulation is that the scatter in the crack growth curves can often be accounted for by allowing for the variability in the threshold term ∆K thr [22,42,44,49,56,57].…”
Section: Theoretical Considerationsmentioning
confidence: 99%